Curative salvage liver transplantation in patients with cirrhosis and hepatocellular carcinoma: An intention‐to‐treat analysis. Issue 1 (15th November 2017) - de Haas, Robbert J.; Lim, Chetana; Bhangui, Prashant; Salloum, Chady; Compagnon, Philippe; Feray, Cyrille; Calderaro, Julien; Luciani, Alain; Azoulay, Daniel
Abstract : The salvage liver transplantation (SLT) strategy was conceived for initially resectable and transplantable (R&T) hepatocellular carcinoma (HCC) patients, to try to obviate upfront liver transplantation, with the "safety net" of SLT in case of postresection recurrence. The SLT strategy is successful or curative when patients are recurrence free following primary resection alone, or after SLT for recurrence. The aim of the current study was to determine the SLT strategy's potential for cure in R&T HCC patients, and to identify predictors for its success. From 1994 to 2012, all R&T HCC patients with cirrhosis were enrolled in the SLT strategy. An intention‐to‐treat (ITT) analysis was used to determine this strategy's outcomes and predictors of success according to the above definition. In total, 110 patients were enrolled in the SLT strategy. Sixty‐three patients (57%) had tumor recurrence after initial resection, and in 30 patients SLT could be performed (recurrence transplantability rate = 48%). From the time of initial resection, ITT 5‐year overall and disease‐free survival rates were 69% and 60%, respectively. The SLT strategy was successful in 60 patients (56%), either by resection alone (36%), or by SLT for recurrence (19%). Preresection predictors of successful SLT strategy at multivariate analysis included Model for End‐Stage Liver Disease (MELD) score >10, and absence of neoadjuvant transarterial chemoembolization (TACE). Additional postresection predictive factors were absence of postresection morbidity, and T‐stage 1‐2 at the resection specimen. Conclusion: The SLT strategy is curative in only 56% of cases. Higher MELD score at inception of the strategy and no pre‐resection TACE are predictors of successful SLT strategy. (Hepatology 2018;67:204‐215).